Phosphorus sources and micronutrients supply methods in an annual cropping system - Ávila, Mateus Olímpyo Tavares de (2020)
Due to the characteristics of the tropical soils and cropping systems used, it is challenging to reduce phosphorus losses, to determine the best method of micronutrient supply, and to choose the nutrient extractor correctly to determining micronutrients. The present work was divided into two articles. In the first article, the aim were evaluate the effect of MAP coated by humic acids and micronutrients on providing phosphorus to plants, as well as the efficiency of efficiency of Mehlich-1, Mehlich-3 and ion exchange resin in phosphorus availability evaluating. In the second article, the aimed to determine the best micronutrient supply method. The experiments were carried out at Muquém farm at Federal University of Lavras, Lavras, MG. A randomized block design in a 4 x 6 factorial scheme was used, with four sources of phosphorus (MAP; MAP coated by humic acids (AH); MAP coated by HA, zinc (Zn), manganese (Mn), copper (Cu ) and boron (B), as well as a control, without phosphorus and micronutrients supply). These treatments were combined with micronutrients supply, being 1- Zn; 2- Mn; 3- Cu; 4- B + Zn + Mn + Cu, both by spraying; 5- B by soil and 6 - control), with 4 repeats. The plots consisted of eight lines in size 6.0 mx 4.8 m, totaling 28.8 m2. The crops used were corn spring/summer (crop year 2016/17), followed by wheat in fall/winter (2016) and soybean spring/summer (2017/18), without irrigation, using cultivars KWS 9004, BRS 264 and M6410 IPRO, respectively. After soybean harvest, in each plot two soil samples were taken from the sowing line and four between the rows, randomly, to the composite sample. The extraction of nutrient contents in the soil was performed by Mehlich-1, Mehlich-3 and ion exchange resin. Leaf samples were collected for the diagnosis of nutritional status in corn and soybean crop. Data were subjected to analysis of variance and significant results to the Scott-Knott test at 5% probability. The coating of MAP by humic acids increases the available phosphorus content in the soil, regardless of the extractor used, the phosphorus leaf content and the yield of corn and soybeans. Mehlich-3 extractor is appropriate for phosphorus extraction in Cerrado soil. Only available soil Cu levels were higher when using MAP coated by micronutrients. There was no change in the available soil contents of any micronutrient when determined by Mehlich-3. The B, Cu, Mn and Zn contents used in the MAP coating do not increase the leaf contents of these micronutrients in diagnostic leaves. The B supply by soil and Cu, Mn and Zn by spraying, provides increase of leaf contents of these nutrients, regardless of the use of phosphate fertilizer coated with these micronutrients.